2013
DOI: 10.1037/a0031748
|View full text |Cite
|
Sign up to set email alerts
|

The criterion-related validity of personality measures for predicting GPA: A meta-analytic validity competition.

Abstract: Interest in the role of personality traits in predicting academic performance outcomes has steadily increased over the last several decades, enough to produce a number of meta-analyses that summarize this research (e.g., Poropat, 2009; Richardson, Abraham, & Bond, 2012). These previous meta-analyses combine a variety of alternative personality measures under the assumption that they all reflect the same personality traits and thus predict outcomes similarly. The current meta-analysis tests this assumption by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
96
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 112 publications
(316 reference statements)
11
96
3
3
Order By: Relevance
“…Higher levels of conscientiousness have been found to consistently predict better job performance and academic achievement (Barrick & Mount, 1991;Chamorro-Premuzic & Furnham, 2003;Lievens et al, 2002;McAbee & Oswald, 2013;O'Connor & Paunonen, 2007;Poropat, 2009;Richardson et al, 2012). Conscientiousness has also been highlighted as an important predictor of performance in medical education (Doherty & Nugent, 2011).…”
Section: Personalitymentioning
confidence: 99%
“…Higher levels of conscientiousness have been found to consistently predict better job performance and academic achievement (Barrick & Mount, 1991;Chamorro-Premuzic & Furnham, 2003;Lievens et al, 2002;McAbee & Oswald, 2013;O'Connor & Paunonen, 2007;Poropat, 2009;Richardson et al, 2012). Conscientiousness has also been highlighted as an important predictor of performance in medical education (Doherty & Nugent, 2011).…”
Section: Personalitymentioning
confidence: 99%
“…Among the Big Five personality traits, conscientiousness is a notable predictor of GPA (McAbee & Oswald, 2013), possibly mediated by a well-organized, careful and self-disciplined style (McCrae & Costa, 1987). The interest in the Big Five model has however overshadowed the exploration of other personality models that may be more suitable for use among adolescents.…”
Section: An Important Factor Impeding a Self-autonomous Learning Procmentioning
confidence: 99%
“…For example, among outcomes examined in their meta-analysis, Barrick et al (2001) found openness to have its strongest relationship with training performance (r D .14). Also, openness consistently has been related to investigative interests , and numerous studies have associated openness with academic performance (e.g., Connelly & Ones, 2010;Furnham, Rinaldelli-Tabaton, & Chamorro-Premuzic, 2011;McAbee & Oswald, 2013;O'Connor & Paunonen, 2007;Poropat, 2009;Richardson, Abraham, & Bond, 2012). However, in many of these studies and across measures, the effect sizes of these relationships have been small.…”
Section: Learning Approach and Performancementioning
confidence: 95%